Evaluating augmented reality in physical education for dyslexic students from the perspectives of teachers and students - Nur Azlina Mohamed Mokmin; Regania Pasca Rassy; Darren Lim Yie (Scientific Reports)
Abstract Students with dyslexia (SWDs), which is a specific learning problem that impairs reading, often experience inadequate academic performance and have a negative perception of themselves in general. However, despite the recognized benefits of Physical Education (PE) classes for physical and psychological development towards SWDs, barriers such as fear of injury, limited resources, and a shortage of trained teachers undermine the inclusivity of PE programs. The present study aims to uncover the issues when teaching PE using the traditional approach and investigate the possible opportunities, challenges, and effectiveness of integrating augmented reality (AR) technology in PE classes. SWDs (n = 22) and PE teachers (n = 2) were selected using purposive sampling, and interview sessions were conducted before and after the intervention. The transcription of the recorded sessions was then analyzed using thematic analysis, and a thematic map was constructed based on the findings. The implementation of AR in PE instruction has the potential to create a more inclusive learning environment, breaking down barriers and promoting the overall well-being of SWDs in Malaysian schools.